Проблеми ідентифікації поняття міжнародного трансферу технологій у науковому дискурсі - Розгон, О. (НДІ ПЗІР НАПрН України, 2023)
Стаття присвячена вирішенню питання ідентифікації поняття міжнародного трансферу технологій у науковому дискурсі. У статті проведено дослідження концептуальних положень щодо обґрунтування сутності категорії «міжнародний трансфер технологій» і бібліографічний аналіз дослідження цієї категорії. Автор звертає увагу на те, що питання міжнародного трансферу технологій знайшли відображення у наукових працях як зарубіжних, так і українських учених. Поняття «міжнародний трансфер технологій» отримало своє широке поширення в юридичній та економічній літературі, однак спостерігаються значущі відмінності поглядів серед вчених щодо його сутності. Здійснене дослідження дозволило дійти висновків про те, що розмаїтість дефініцій поняття «міжнародний трансфер технологій» демонструє наявність різносторонніх підходів до розуміння суті самої проблеми міжнародного трансферу технологій. Визначено, що всі підходи є обґрунтованими й актуальними та їх використання залежить від конкретного аспекту, під яким розглядається міжнародний трансфер технологій. У результаті дослідження встановлено, що задля вдосконалення категорії «міжнародний трансфер технологій» його поняття має бути зафіксовано у Законі України «Про державне регулювання діяльності у сфері трансферу технологій» шляхом внесення змін до ст. 1 цього Закону. Проведене дослідження дозволило зробити висновок, що міжнародний трансфер технологій як категорія є базовою, комплексною, складною дефініцією, яка характеризує правовідносини, що виникають між суб’єктом господарювання або іншим учасником відносин та іноземним суб’єктом, які є резидентом і нерезидентом країни відповідно, пов’язані зі створенням, передачею прав і втіленням технологій, укладенням певних договорів, які будуть спрямовані на передачу прав на технологію чи інформації про технологію або матеріальне втілення (відтворення) технології. Problem setting. The issues of international technology transfer are reflected in the scientific works of both foreign and Ukrainian scientists. The concept of «international technology transfer» is widely used in the legal and economic literature, but there are significant differences of opinion among scholars regarding its essence. Analysis of recent researches and publications. Among Ukrainian scientists, international technology transfer is considered more in the economic literature: H. O. Bak, O. B. Salikhova, A. S. Bura, O. O. Bakalinska, Y. Yakubivska. Various foreign scientists have considered international technology transfer in their works. In particular, R. D. Robinson and and G. F. Jewett, Kasych A. and Medvedeva G., C. Liu and S. Yan, Sepúlveda C. I. and Ocampos J. A., Lundquist D. G. and Grosse R. Target of the research is to identify the views on the category of «international technology transfer» existing in the scientific literature and to study them in order to specify the nature of international technology transfer. Article’s main body. The article is devoted to the issue of identifying the concept of international technology transfer in the scientific discourse. The article studies the conceptual provisions for substantiating the essence of the category of «international technology transfer» and conducts a bibliographic analysis of the studies of this category. The author emphasizes that the issues of international technology transfer are reflected in the scientific works of both foreign and Ukrainian scholars. The concept of «international technology transfer» is widespread in the legal and economic literature, but there are significant differences of opinion among scholars regarding its essence. This study has led to the conclusion that the variety of definitions of the concept of «international technology transfer» demonstrates the existence of diverse approaches to understanding the essence of the problem of international transfer of technology. It is determined that all approaches are reasonable and relevant and their use depends on the specific aspect under which international technology transfer is considered. The study found that in order to improve the category of «international technology transfer», its concept should be fixed in the Ukrainian Law «On State Regulation of Activities in the Field of Technology Transfer» by amending Article 1 of this Law. Conclusions and prospects for the development. The study has led to the conclusion that international technology transfer as a category is a basic, complex and complex definition that characterizes legal relations arising between a business entity or other party to the relationship and a foreign entity, which is a resident and non-resident of the country, respectively, and related to the creation, transfer of rights and implementation of technology, as well as the conclusion of certain agreements aimed at transferring rights to technology or information about technology, or material embodiment (reproduction) of technology in the field of technology transfer.
Keywords: міжнародний трансфер технологій; інноваційний процес; суб’єкти; international technology transfer; innovation process; subjects; transfer; agreement